α-Synuclein Controls Mitochondrial Calcium Homeostasis by Enhancing Endoplasmic Reticulum-Mitochondria Interactions - Calì, Tito (American Society for Biochemistry and Molecular Biology, 2012)
α-Synuclein has a central role in Parkinson disease, but its physiological function and the mechanism leading to neuronal degeneration remain unknown. Because recent studies have highlighted a role for α-synuclein in regulating mitochondrial morphology and autophagic clearance, we investigated the effect of α-synuclein in HeLa cells on mitochondrial signaling properties focusing on Ca(2+) homeostasis, which controls essential bioenergetic functions. By using organelle-targeted Ca(2+)-sensitive aequorin probes, we demonstrated that α-synuclein positively affects Ca(2+) transfer from the endoplasmic reticulum to the mitochondria, augmenting the mitochondrial Ca(2+) transients elicited by agonists that induce endoplasmic reticulum Ca(2+) release. This effect is not dependent on the intrinsic Ca(2+) uptake capacity of mitochondria, as measured in permeabilized cells, but correlates with an increase in the number of endoplasmic reticulum-mitochondria interactions. This action specifically requires the presence of the C-terminal α-synuclein domain. Conversely, α-synuclein siRNA silencing markedly reduces mitochondrial Ca(2+) uptake, causing profound alterations in organelle morphology. The enhanced accumulation of α-synuclein into the cells causes the redistribution of α-synuclein to localized foci and, similarly to the silencing of α-synuclein, reduces the ability of mitochondria to accumulate Ca(2+). The absence of efficient Ca(2+) transfer from endoplasmic reticulum to mitochondria results in augmented autophagy that, in the long range, could compromise cellular bioenergetics. Overall, these findings demonstrate a key role for α-synuclein in the regulation of mitochondrial homeostasis in physiological conditions. Elevated α-synuclein expression and/or eventually alteration of the aggregation properties cause the redistribution of the protein within the cell and the loss of modulation on mitochondrial function.